Long Use Of KB Implant With Increased Weight On KB Accepters Implant - Sudawin, Sudawin; Rosmiyati, Rosmiyati; Evayanti, Yulistiana (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Latar Belakang: Keluarga Berencana (KB) merupakan salah satu layanan kesehatan preventif paling dasar dan utama bagi perempuan. Cakupan peserta KB implan menurut metode kontrasepsi modern pada tahun 2020 adalah 8,5%. Penggunaan kontrasepsi implan dapat menimbulkan beberapa efek samping dan masalah, salah satunya adalah kenaikan berat badan.Tujuan: Untuk mengetahui hubungan antara lama penggunaan KB Implan dengan peningkatan berat badan pada akseptor KB Implan di Puskesmas Rawat Inap Rejo Katon tahun 2022.Metode: Jenis penelitian ini adalah kuantitatif dengan rancangan penelitian observasi analitik dengan rancangan cross sectional. Populasi dalam penelitian ini adalah seluruh akseptor KB Implan di Puskesmas Rawat Inap Rejo Katon tahun 2019-2021 dengan jumlah 241 orang dan sampel sebanyak 211 orang. Teknik pengambilan sampel dalam penelitian ini adalah purposive sampling. Analisis data menggunakan chi square.Hasil: Lama penggunaan KB Implan pada akseptor KB Implan didapatkan 149 (70,6%) responden menggunakan KB implan 1 tahun dan peningkatan berat badan pada akseptor KB Implan didapatkan 140 (66,4%) responden mengalami peningkatan berat badan. Hasil uji chi square didapatkan pvalue 0,000 0,05. Kesimpulan: Terdapat hubungan antara lama penggunaan KB Implan dengan peningkatan berat badan pada akseptor KB Implan di Puskesmas Rawat Inap Rejo Katon tahun 2022. Saran bagi pengguna KB Implan jangka panjang untuk menjaga berat badan dengan mengatur pola dan frekuensi makan serta menyeimbangkannya dengan olahraga teratur. Kata Kunci: Lama penggunaan, KB Implan, Berat Badan ABSTRACT Background: Family Planning (KB) is one of the most basic and main preventive health services for women. The coverage of implant family planning participants according to modern contraceptive methods in 2020 is 8.5%. The use of implant contraceptives can cause several side effects and some problems, one of which is weight gain.Purpose: To determine the relationship between the duration of the use of KB Implants with increased body weight in KB Implant acceptors at the Rejo Katon Inpatient Health Center in 2022.Methods: This type of research is quantitative with a research designanalytic observation with cross sectional design. The population in this study isall acceptors of KB Implants at the Rejo Katon Inpatient Health Center in 2019-2021 with a total of 241 people and a sample of 211 people. The sampling technique in this study ispurposive sampling.Data analysis usingchisquare.Results: The duration of the use of KB Implants in KB Implant acceptors obtained 149 (70.6%) respondents using KB implants 1 year and the increase in body weight in KB Implant acceptors obtained 140 (66.4%) respondents experienced an increase in body weight. Test resultschi squareget pvalue0.000 0.05.Conclution: there is a relationship between the length of use of KB Implants and the increase in body weight in KB Implant acceptors at the Rejo Katon Inpatient Health Center in 2022. Suggestionsusers of long-term KB implants to maintain their weight by adjusting the pattern and frequency of eating and balancing it with regular exercise. Keywords : Length of use, KB implants, Weight